Motor‐symptom laterality affects acquisition in Parkinson's disease: A cognitive and functional magnetic resonance imaging study. Issue 7 (8th May 2017) - Huang, Pei; Tan, Yu‐Yan; Liu, Dong‐Qiang; Herzallah, Mohammad M.; Lapidow, Elizabeth; Wang, Ying; Zang, Yu‐Feng; Gluck, Mark A.; Chen, Sheng‐Di
ABSTRACT: Background and Objectives : Asymmetric onset of motor symptoms in PD can affect cognitive function. We examined whether motor‐symptom laterality could affect feedback‐based associative learning and explored its underlying neural mechanism by functional magnetic resonance imaging in PD patients. Methods : We recruited 63 early‐stage medication‐naïve PD patients (29 left‐onset medication‐naïve patients, 34 right‐onset medication‐naïve patients) and 38 matched normal controls. Subjects completed an acquired equivalence task (including acquisition, retention, and generalization) and resting‐state functional magnetic resonance imaging scans. Learning accuracy and response time in each phase of the task were recorded for behavioral measures. Regional homogeneity was used to analyze resting‐state functional magnetic resonance imaging data, with regional homogeneity lateralization to evaluate hemispheric functional asymmetry in the striatum. Results : Left‐onset patients made significantly more errors in acquisition (feedback‐based associative learning) than right‐onset patients and normal controls, whereas right‐onset patients performed as well as normal controls. There was no significant difference among these three groups in the accuracy of either retention or generalization phase. The three groups did not show significant differences in response time. In the left‐onset group, there was an inverse relationship between acquisition errors and regional homogeneity in the right dorsal rostral putamen. There were no significant regional homogeneity changes in either the left or the right dorsal rostral putamen in right‐onset patients when compared to controls. Conclusions : Motor‐symptom laterality could affect feedback‐based associative learning in PD, with left‐onset medication‐naïve patients being selectively impaired. Dysfunction in the right dorsal rostral putamen may underlie the observed deficit in associative learning in patients with left‐sided onset.© 2016 International Parkinson and Movement Disorder Society